Evolution of Information Management Discipline and Information Industry in Malaysia - Fazli Sahari, Mohd; Farik Mat Yatin, Saiful; Md. Zain, Kamarulzaidi; Arni Abdul Hadi, Hazulia; Nabila Azli, Nurul; Akmar Ismail, Saidatul; Nor Haliza Wan Mokhtar, Wan (International Journal of Engineering and Technology, 2018)
Information is very much related to the movement of industry. It is even so close with the development of Malaysia. Information industry have to be understood and realized by both government and private industry its importance and significant towards the development of Malaysia economy and its tertiary education. Information Technology and Information Management is an interrelated field and cannot be separated. This article discusses the problems of IT, development of library and information science education, development, importance of ICT and Internet as new media in MalaysiaÂ Â